Effect of thermo-mechanical load cycling on silorane-based composite restorations - Sanches Borges, Ana Flavia; Santos, Juliete de Sousa; Ramos, Carla Mueller; Ishikiriama, Sergio Kiyoshi; Shinohara, Mirela Sanae [UNESP] (Japanese Soc Dental Materials Devices, 2012)
The aim of this study was to compare the formation of marginal gaps after thermo-mechanical load cycling, between silorane-based and methacrylate-based restorations. Standardized class II cavities were made in 10 permanent human third molars that were restored with the adhesive system Clearfil SE Bond+composite Filtek Z-350 (Methacrylates) and with the composite bonding Filtek P90+P90 (Siloranes), respectively. After 24 h of storage in 100% humidity at 37 degrees C, the restoration margins were stained, photographed, and evaluated. The gap length was calculated as the percentage of the total length of the margins. Thereafter, the specimens were tested by a thermo-mechanical machine and the marginal gap formation of the specimens was re-evaluated. The results were expressed as percentages of gaps and were submitted to a Mann Whitney test at 5% level of significance. Methacrylates showed a statistically significant higher percentage of gaps than Siloranes, both before and after cycling.
Keywords: Composite; Shrinkage; Marginal gap